Approach in Educational Management for Developing Teacher Professionalism at SDN 2 Lendang Kunyit - Nurul Aulia; Mohamad Mustari (Insights: Journal of Primary Education Research, 2024)
A collaborative approach in educational management in elementary schools is an important key to developing teacher professionalism. This article examines the implementation of a collaborative approach at SDN 2 Lendang Kunyit in improving the quality of teaching. Through qualitative methods with case studies, data was obtained from interviews with school principals and teachers as well as observations of collaborative activities. The research results show that group discussions, collaborative supervision, joint training, and professional learning communities (KKG) are effective in improving teachers' pedagogical and managerial competencies. Collaboration between teachers and principals in reflection-based supervision strengthens learning innovation and joint problem solving. Although challenges such as time constraints and resistance to change were encountered, this approach was able to overcome them through good time management and active support from the principal. Other positive impacts include increased student motivation and learning outcomes, indicating that collaboration at the teacher level can directly influence the quality of learning. Overall, implementing a collaborative approach at SDN 2 Lendang Kunyit can be an effective model for improving teacher professionalism and the quality of education in elementary schools.